2019
DOI: 10.4491/eer.2019.269
|View full text |Cite
|
Sign up to set email alerts
|

Energy and nutrient recovery from agro-wastes: Rethinking their potential possibilities

Abstract: Agricultural sector has inescapably drawn attention towards itself due to growing concern over population explosion, changing climate and depletion of resources. Advancements in technology have caused rapid boost in farm productivity and hence huge production of agro-wastes. There have been massive deteriorating impacts of agro-wastes on existing environmental conditions, creating wide scale environmental pollution as well as biodiversity loss. Since, agro-wastes have huge potential in the form of energy and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 123 publications
2
10
1
Order By: Relevance
“…142 A comprehensive study on various bio-based sources for conductive carbon has been recently made by Zia et al, 143 including agricultural crops, energy crops, crop residue, forest, forestry residue, aquatic crops, municipal waste and industrial waste, confirming the high potential application of these materials in sectors for energy storage and harvesting. Elemental composition in terms of nitrogen content also confirmed values of 1-5% in agricultural 144 and food wastes. 145 It has also been demonstrated that green mode-based synthesized nanoparticles exert antibacterial, antioxidant, and antifungal activity against a plethora of pathogens for food packaging purposes, facilitating a simple, alternative, interactive and reliable technology with positive feedback for the food industries and packaging markets.…”
Section: Biowaste Feedstocks For Nanofillerssupporting
confidence: 54%
See 1 more Smart Citation
“…142 A comprehensive study on various bio-based sources for conductive carbon has been recently made by Zia et al, 143 including agricultural crops, energy crops, crop residue, forest, forestry residue, aquatic crops, municipal waste and industrial waste, confirming the high potential application of these materials in sectors for energy storage and harvesting. Elemental composition in terms of nitrogen content also confirmed values of 1-5% in agricultural 144 and food wastes. 145 It has also been demonstrated that green mode-based synthesized nanoparticles exert antibacterial, antioxidant, and antifungal activity against a plethora of pathogens for food packaging purposes, facilitating a simple, alternative, interactive and reliable technology with positive feedback for the food industries and packaging markets.…”
Section: Biowaste Feedstocks For Nanofillerssupporting
confidence: 54%
“…142 A comprehensive study on various bio-based sources for conductive carbon has been recently made by Zia et al , 143 including agricultural crops, energy crops, crop residue, forest, forestry residue, aquatic crops, municipal waste and industrial waste, confirming the high potential application of these materials in sectors for energy storage and harvesting. Elemental composition in terms of nitrogen content also confirmed values of 1–5% in agricultural 144 and food wastes. 145…”
Section: Biowaste Feedstocks For Nanofillerssupporting
confidence: 53%
“…Certification, fortification, and labeling increase farmers' willingness to accept and pay for HEDM [16,45]. Comlizer, an example of a blend of compost and inorganic fertilizers developed in Ghana, reported higher nitrogen and phosphorus uptake, soil organic matter, nutrient uptake, water use efficiency, and crop yield than chemical fertilizers [129,130]. Pelletizing compost, for instance, is important as it improves product structure and bulk density, which reduce the costs associated with handling, transport, and storage [45,131,132].…”
Section: Implications Of the Study For Research Policy And Developmmentioning
confidence: 99%
“…Emphasis on reducing fossil-fuel dependency and mining of limited natural resources has driven an enhanced attention towards nutrient recovery from biomass streams such as animal manure, household and food waste, and sewage sludge [5][6][7][8][9][10]. The concept of a circular economy deeply highlights the significance of nutrient recovery, with an aim to prevent detrimental environmental effects such as soil salinity, eutrophication of water bodies, accumulation of nitrates in groundwater, heavy metal accumulation in soil, and release of greenhouse gases [11,12].…”
Section: Introductionmentioning
confidence: 99%